Práctica de enseñanza con una perspectiva intercultural. Análisis de caso en la Unidad E ducativa intercultural bilingüe “Dolores Cacuango”, en segundo año de educación básica. - Lanchimba Farinango, José Bayardo (2016)
The very vital work is being done research where most fundamentally describes the pedagogical aspect of the intercultural educational practices of the Education Unit in order to learn about and understand the problematic and complex performance of the actors involved on the construction of the intercultural education activities within the educational establishment framed in standards of educational work. Community life and coexistence between theoretical knowledge of education has given the opportunity to provide many weaknesses in the daily practice of teaching with an intercultural vision based on the daily lives and the theoretical part with which we check the statements and raising the new approaches to a new educational institutions who support the real development of education, the same as promoting a change of educational model. Today's proposal is to address a new education, promote the development of individual and collective skills in practice and exchange of knowledge to transform and lead to the benefit of the peoples and nationalities of our country. Finally Intercultural Bilingual Education (IBE) needs the commitment and contribution of all actors shaped in various sectors of augmenting the new educational model based intercultural ideological principles of the society Ecuadorian.